The Cameroon Condition. - Ngwane, George (Langaa RPCIG, 2012)
The Cameroon Condition brings together three seminal essays by George Ngwane, one of the most renowned, committed and daring Anglophone Cameroon writers. ìThe Mungo Bridge, î is a stinging indictment of the tenuous relations between La Republique du Cameroun and the Southern Cameroons ñ a marriage gone sour right from the honeymoon. It raises hard questions on the failed union, and is uncompromisingly courageous in the solutions it proposes. This popular essay was first published at a time when it was risky to be open and critical, especially on what has come to be known as The Anglophone Probl.